Modern Dance Center Di Batam Dengan Pendekatan Arsitektur Ekspresionis - Allany Syahidanilla Darojat; Yohannes Firzal; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Modern dance competition in Batam increases the interest of the community and tourists about the dance, but in Batam there is not a forum that can provide facilities for training, recreation, performances, and sports. Community need a place that can provide these facilities. The Modern Dance Center in Batam is a facilities for dance activities such as, education, performance, information, and other dance applications. This method uses the Expressionist Architecture approach so the building can express the emotions conveyed and can be felt by the viewer, so the expression is not only seen from the performances displayedbut also from the modern dance center building. In addition it is not only a building that provides facilities but also as a work of art. Through the concept of battle dance, buildings can show the strengths of styles and the differences between modern dance styles. So theexpression of freedom can be seen in buildings. There are 3 functions in this modern dance center building, namely: main function, supporting function, complementary function. The main functions are education and recreation there are training studios and auditoriums,supporting functions as commercials there are foodcourt and retail, and complementary functions there are managers and services.Keyword :Batam, Modern Dance Center, Expressionist Architecture